FUN LEARNING: CLASS MANAGEMENT METHOD TO CREATE A CONDUCIVE ATMOSPHERE FOR STUDENT LEARNING - Dzulfahmi, A. Adib; Aimmah, Tania Nafida (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Religious education is left behind even though it is an essential element, there is 53.57% of Indonesian Muslims cannot read the Qur’an. And classroom management in religious education is an activity or effort to overcome a problem, which aims to create and maintain a classroom atmosphere that supports the program Learning goes effectively. Effective learning can be done by: Creating a conducive environment during the learning process. In order to create an effective learning atmosphere, namely by creating a sense of comfort, fun and motivation so that it becomes a driver and encouragement for student learning. Therefore, success in the student learning process must be supported by teachers who are competent in managing the class and creating a conducive learning environment. This research adopts field research methods, especially qualitative approach with a focus on qualitative description. This research tries to find out more optimal implementation of classroom management using the application of fun learning in classroom management to create a conducive atmosphere for student learning. And in this study it was found that the using of puzzle media can make the classroom better conducive atmosphere and make it easier for teachers to control students, and also learning using the BCM method (singing, story, and recitation) can increase the enthusiasm of students learning.